1984
DOI: 10.1002/qua.560260720
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glyoxalase Iin vitro by flavones

Abstract: Based on previous research from these laboratories various structural analogs of 3-hydroxyflavone were tested for inhibition of glyoxalase 1 (S-lactoyl-glutathione methylglyoxal lyase, isomerizing; EC 4.4.1.5). The substrate of glyoxalase I (Glo I), methylglyoxal, has growth inhibitory properties. Glo I was purified 7000-fold from human red blood cells, and the concentration of various flavones was determined for 50% inhibition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…1158 Other transition state mimetic inhibitors include coumarins and flavones, with the most active being 7,8-dihydroxy-4-phenylcoumarin (Glo1i-8, human Glo1 IC 50 = 3.5 μM) and myricetin (human Glo1 IC 50 = 5 μM). 1159,1167 Further exploration of transition state mimetics was performed analyzing methylated and nonmethylated enediol transition state mimics, which in combination with spectral data indicated that the enediol mimicking moiety of many transition state based inhibitors is involved in metal coordination. 1171 A computational analysis of previously published transition state mimics, demonstrated that the most important motif for activity was a α-hydroxy-α,β-unsaturated carbonyl group attached to a fused ring carbon, such as that present in flavones like myricetin.…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%
See 1 more Smart Citation
“…1158 Other transition state mimetic inhibitors include coumarins and flavones, with the most active being 7,8-dihydroxy-4-phenylcoumarin (Glo1i-8, human Glo1 IC 50 = 3.5 μM) and myricetin (human Glo1 IC 50 = 5 μM). 1159,1167 Further exploration of transition state mimetics was performed analyzing methylated and nonmethylated enediol transition state mimics, which in combination with spectral data indicated that the enediol mimicking moiety of many transition state based inhibitors is involved in metal coordination. 1171 A computational analysis of previously published transition state mimics, demonstrated that the most important motif for activity was a α-hydroxy-α,β-unsaturated carbonyl group attached to a fused ring carbon, such as that present in flavones like myricetin.…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%
“…More active inhibitors included maltol (Glo1i-3, yeast Glo1, K i = ∼400 μM), squaric acid (Glo1i-4, human Glo1, IC 50 = 120 μM), and 2,3-dihydroxy-benzoic acid (Glo1i-5, IC 50 = 280 μM). , An expansion of potential transition state mimetics, including 2,3-dihydroxypyridine (Glo1i-6, human Glo1, IC 50 = 530 μM) and polyphenolic benzohydroxamic acids such as 2,3,4-trihydroxybenzohydroxamic acid (Glo1i-7, human Glo1, IC 50 = 210 μM), were reported . Other transition state mimetic inhibitors include coumarins and flavones, with the most active being 7,8-dihydroxy-4-phenylcoumarin (Glo1i-8, human Glo1, IC 50 = 3.5 μM) and myricetin (human Glo1, IC 50 = 5 μM). , Further exploration of transition state mimetics was performed by analyzing methylated and nonmethylated enediol transition state mimics, which in combination with spectral data indicated that the enediol mimicking moiety of many transition state-based inhibitors is involved in metal coordination . A computational analysis of previously published transition state mimics demonstrated that the most important motif for activity was an α-hydroxy-α,β-unsaturated carbonyl group attached to a fused ring carbon, such as that present in flavones like myricetin .…”
Section: Lyases (Ec 4x)mentioning
confidence: 99%
“…The latter was a deviation from the original hypothesis which suggested compartmentalization of promine. A postdoctoral investigator in the same lab later found evidence that the natural inhibitor was a avonoid [4]. Also, another student working with wild carrot cells in suspension culture found that somatic embryogenesis therein was enhanced by the addition of buthionine sulfoximine [BSO, a speci c inhibitor of glutathione (GSH) biosynthesis] whereas GSH addition blocked somatic embryogenesis [5].…”
Section: Introductionmentioning
confidence: 99%